Pengaruh Laba Kotor, Kebijakan Dividen dan Profitabilitas Terhadap Harga Saham Dengan Company Social Responsibility Sebagai Variabel Pemoderasi (Studi Empiris Perusahaan yang Terindeks Kompas 100 Tahun 2014-2016) - Dhian Andanarini Minar Savitri; Mirna Dyah Praptitorini S.; Ita Nur (JURNAL SOSIAL EKONOMI DAN HUMANIORA, 2018)
This study is aimed at knowing the effect of CSR, gross profit, dividend police and profitability to the stock price of indexs KOMPAS 100 in BEI period 2014-2016. Date used is secondary date sheped time series in year 2014-2016 with download information in stock exchange Indonesia Technique analyzed using the multiple linier regression with SPSS program. The research results show that partiall, gross profit has a positive effect on stock prices, but dividend police and profitability has no effect on stock prices. CSR doesn’t moderate gross profit, dividend policy and profitability.